2017
DOI: 10.1093/bja/aex089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of peripheral and central sensitization after dorsal root ganglion intervention in patients with unilateral lumbosacral radicular pain: a prospective pilot study

Abstract: The study demonstrates that patients with unilateral radicular low back pain who receive dorsal root ganglion interventions show changes in pressure pain thresholds and conditioned pain modulation that are consistent with a 'normalization' of peripheral and central sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
2
19
1
5
Order By: Relevance
“…We have previously characterized CPM and PPT's in patients with unilateral lumbosacral pain undergoing dorsal root ganglion block. We have demonstrated that both CPM and PPT's (measured in the painful leg) improved significantly following the block . There have been limited studies, which looked to establish a phenotypic profile or a biomarker in predicting the response to SCS .…”
Section: Discussionmentioning
confidence: 92%
“…We have previously characterized CPM and PPT's in patients with unilateral lumbosacral pain undergoing dorsal root ganglion block. We have demonstrated that both CPM and PPT's (measured in the painful leg) improved significantly following the block . There have been limited studies, which looked to establish a phenotypic profile or a biomarker in predicting the response to SCS .…”
Section: Discussionmentioning
confidence: 92%
“…After reading the titles and abstracts of the articles and assessing them for eligibility based on the full-text articles, 63 publications were finally included in this review. Among the included studies, PRF was applied for radicular pain from cervical spinal diseases in 13 studies (1,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and lumbar spinal diseases in 17 studies (2,15,19,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), respectively. PRF was applied for postherpetic neuralgia in 6 studies (39)(40)(41)(42)(43)(44), trigeminal neuralgia in 14 studies (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, so far, 16 studies have evaluated the effects of PRF to the DRG in patients with lumbosacral radicular pain induced by herniated discs or spinal stenosis (2,15,19,20,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Among the 16 studies, 5 were RCTs (2,19,28,33,34), 3 were prospective observational studies (30,36,37), 7 were retrospective studies (15,20,27,29,32,35,38), and one was a case study (31). Although the degrees of pain relief were presented differently in each study, generally, lumbosacral radicular pain was successfully reduced after applying PRF to the DRG.…”
Section: Efficacy Of Prf In Peripheral Neuropathic Painmentioning
confidence: 99%
“…Our group has demonstrated an alteration in peripheral and central sensitization response with a significant improvement at 4 weeks following lumbar L4 DRG target for radicular neuropathic pain with 45 Volts pulsed radiofrequency . Recently, laser evoked potential measurements (a surrogate marker of brain cortical activity) have demonstrated a negative correlation with success of DRG stimulation for peripheral neuropathic pain in one and six months, with DRG stimulation being able to restore the laser evoked potential to normal values .…”
Section: Introductionmentioning
confidence: 90%